Effect of five doses of plant waste and animal manure in the production of compost in the canton of La Maná - Salazar Saltos, Alex Enrique (2024)
The production of organic fertilizers is crucial for the reuse of organic waste, reducing pollution and avoiding harmful emissions. The Technical University of Cotopaxi, through its Linkage Project, sought to improve waste management through the production of compost. A study was carried out in the experimental center "La Playita" in the Canton of La Maná, using 5 treatments that combined vegetable waste and bovine manure. Each treatment was replicated 4 times, using a randomized, 95% Tukey complete block design. Variables such as temperature, pH, electrical conductivity, harvest volume and mineral fertility of the fertilizer were evaluated for 15 weeks. Temperature peaked in week 3, with values between 37.45 °C and 38.95 °C in all treatments, while pH showed a tendency to decrease with increasing temperature, becoming neutralized in week 15. The final electrical conductivity was within the optimal range for good compost. In terms of harvest volume, the T5 treatment obtained the lowest yield, while the T2 showed better nutritional results in terms of N and K, and the T5 stood out in P and Ca.